Effects of high-intensity intermittent exercise on glucose and lipid metabolism in type 2 diabetes patients: a systematic review and meta-analysis - Feng, Jingwen; Zhang, Qiuhua; Chen, Baoyi; Chen, Jinping; Wang, Wenjun; Hu, Yuhang; Yu, Jiabin; Huang, Huiming (Frontiers in Endocrinology, 2024)
Objective: To evaluate the effects of high-intensity interval training (HIIT) on glycolipid metabolism among type 2 diabetes patients.Methods: HIIT is consistent with an exercise program (65%-90%VO2max or 75%-95% HRmax; exercise cycle≥2 weeks; frequency ≥ 2 times/week). A meta-analysis was conducted utilizing the random effects model to synthesize the data.Results: A total of 22 RCT studies with 1034 diabetic patients were included. Compared to moderate-intensity aerobic exercise or conventional controls, HIIT yields noteworthy effects on FBG